Elasto-plastic stress analysis of the triaxial test specimen - Sawate Klainatorn
A finite element computer program in this thesis was developed based on "General Purpose Finite Element System Solver (GEFESS)" by Chaiyuth Foophow to study the distributions of stress and strain induced in cylindrical specimen of earth media. The logic used in elasticity routines of unconfirmed pressure test was verified by comparing the computed stress-strain results given by Chiyyarath V. Girijavallabhan and this study. Furthermore, the elasto-plastic stress distributions were obtained by the triaxial test.